X-Linked Sensorineural Hearing Loss: A Literature Review - Corvino, Virginia; Apisa, Pasqualina; Malesci, Rita; Laria, Carla; Auletta, Gennaro; Franze, Annamaria (Current Genomics, 2018)
Sensorineural hearing loss is a very diffuse pathology (about 1/1000 born) with several types of transmission. X-linked hearing loss accounts for approximately 1% - 2% of cases of nonsyndromic forms, as well as for many syndromic forms. To date, six loci (DFNX1-6) and five genes (PRPS1 for DFNX1, POU3F4 for DFNX2, SMPX for DFNX4, AIFM1 for DFNX5 and COL4A6 for DFNX6) have been identified for X-linked non-syndromic hearing loss. For the syndromic forms, at least 15 genes have been identified, some of which are also implicated in non-syndromic forms. Moreover, some syndromic forms, presenting large chromosomal deletions, are associated with mental retardation too. This review presents an overview of the currently known genes related to X-linked hearing loss with the support of the most recent literature. It summarizes the genetics and clinical features of X-linked hearing loss to give information useful to realize a clear genetic counseling and an early diagnosis. It is important to get an early diagnosis of these diseases to decide the investigations to predict the evolution of the disease and the onset of any other future symptoms. This information will be clearly useful for choosing the best therapeutic strategy. In particular, regarding audiological aspects, this review highlights risks and benefits currently known in some cases for specific therapeutic intervention.
Keywords: Hearing aids